2018
DOI: 10.1016/j.dib.2018.08.155
|View full text |Cite
|
Sign up to set email alerts
|

Data on Manuka Honey/Gellan Gum composite hydrogels for cartilage repair

Abstract: This work contains original data supporting our research paper “Antibacterial effectiveness meets improved mechanical properties: Manuka Honey/Gellan Gum composite hydrogels for cartilage repair”, Bonifacio et al., in press [1], in which innovative composite hydrogels, based on Gellan Gum/Manuka honey/Halloysite nanotubes were described as biomaterials for cartilage regeneration. Here the composites were further examined by means of Fourier Transform Infrared Spectroscopy, in Attenuated Total Reflectance mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…El-Malek et al [31] incorporated 20% (v/v) MH into a chitosan-gelatin hydrogel, resulting in antibacterial properties to S. aureus , Streptococcus pyogenes , Acinetobacter baumannii , Pseudomonas aeruginosa , and Proteus mirabilis . Similarly, two studies completed by Bonifacio et al [32,33] examined a MH/gellan gum composite hydrogel which led to the inhibition of both S. aureus and S. epidermidis clinical isolates. As this was targeting cartilage repair, mesenchymal stem cells were also seeded on the scaffolds and, in addition to no cytotoxic effect, collagen II expression and synthesis of glycosaminoglycans (GAGs) and proteoglycans was observed.…”
Section: Introductionmentioning
confidence: 99%
“…El-Malek et al [31] incorporated 20% (v/v) MH into a chitosan-gelatin hydrogel, resulting in antibacterial properties to S. aureus , Streptococcus pyogenes , Acinetobacter baumannii , Pseudomonas aeruginosa , and Proteus mirabilis . Similarly, two studies completed by Bonifacio et al [32,33] examined a MH/gellan gum composite hydrogel which led to the inhibition of both S. aureus and S. epidermidis clinical isolates. As this was targeting cartilage repair, mesenchymal stem cells were also seeded on the scaffolds and, in addition to no cytotoxic effect, collagen II expression and synthesis of glycosaminoglycans (GAGs) and proteoglycans was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, scaffolds represent an important help for wound and tissue repair [110], and honey can be very useful for scaffold synthesis [111]. Scaffolds created with manuka honey and gellan gum are able to promote cartilage healing, stimulating the growth and differentiation of chondroblasts [112,113].…”
Section: Honey and "Green Chemistry"mentioning
confidence: 99%
“…To initially determine the best method to incorporate MH into the 4%-chitosan-gelatin scaffolds, MH was added to the scaffolds at different stages using four mixing methods. Note that the concentration of MH used (0, 1, 5, or 10%) was based on previous work by our group and others, demonstrating the advantages of these different concentrations related to bacterial clearance and scaffold properties [17,19,20,37].…”
Section: Scaffold Fabrication Optimizationmentioning
confidence: 99%
“…This study tested scaffolds against E. coli, P. aeruginosa, S. aureus, Bacillus subtilis, and the fungus Candida albicans, concluding that chitosan-lactic acid combined with 6% MH was effective against S. aureus and E. coli. Similarly, Bonifacio et al [19] combined 2% MH with six types of gellangum-based hydrogels, which were found to be effective against S. aureus and Staphylococcus epidermidis. Our group also incorporated MH into silk-based cryogels and hydrogels at 1, 5, and 10% concentrations and evaluated these scaffolds against biofilm formation by S. aureus [15].…”
Section: Introductionmentioning
confidence: 99%